PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI DALAM KAITANNYA DENGAN KEPUASAN KERJA KARYAWAN - Calvin Andrian Gunawan; Wilson Bangun (Institut Pendidikan Tapanuli Selatan, 2024)
Employee Job Satisfaction is a determinant of the success of a company. This is because the company is filled with people who work to their potential and contribute to achieving company goals. Employee Job Satisfaction can be influenced by various factors, including Transformational Leadership and Motivation. The research was conducted at PT Garuda Mas Semesta with the intention of examining the effect of Transformational Leadership and Motivation and simultaneously on Employee Job Satisfaction. This research was conducted on 60 permanent employees or equivalent staff. Quantitative approach with explanatory research type used in this research. In collecting data using questionnaire techniques with Likert scale measurements. Data processing in this study uses the Partial Least Square (PLS) method with the SmartPLS application. The results in this study explain the significant influence of the Motivation variable on Employee Job Satisfaction and Transformational Leadership and Motivation simultaneously on Employee Job Satisfaction. Different results are shown by the Transformational Leadership variable on Employee Job Satisfaction which shows an influence but not significant.